Multiplex biomarker techniques: methods and applications - Guest, Paul C. (Methods in molecular biology, 2017)
Application of Multiplex Biomarker Approaches to Accelerate Drug Discovery and Development -- The Application of Multiplex Biomarker Techniques for Improved Stratification and Treatment of Schizophrenia Patients -- Multiplex Biomarker Approaches in Type 2 Diabetes Mellitus Research -- LC-MSE, Multiplex MS/MS, Ion Mobility, and Label-Free Quantitation in Clinical Proteomics -- Phenotyping Multiple Subsets of Immune Cells In Situ in FFPE Tissue Sections: An Overview of Methodologies -- Identification and Clinical Translation of Biomarker Signatures: Statistical Considerations -- Opportunities and Challenges of Multiplex Assays: A Machine Learning Perspective -- Multiplex Analyses Using Real-Time Quantitative PCR -- Multiplex Analysis Using cDNA Transcriptomic Profiling -- Multiplex Single Nucleotide Polymorphism Analyses -- Pulsed SILAC as a Proteomic Approach for miRNA Targets Identification in Cell Culture -- Blood Bio-Sampling Procedures for Multiplex Biomarkers Studies -- Multiplex Immunoassay Profiling -- Multiplex Sequential Immunopreciptation of Insulin Secretory Granule Proteins from Radiolabeled Pancreatic Islets -- Two Dimensional Gel Electrophoresis of Insulin Secretory Granule Proteins from Biosynthetically-Labeled Pancreatic Islets -- Depletion of Highly Abundant Proteins of the Human Blood Plasma: Applications in Proteomics Studies of Psychiatric Disorders -- Simultaneous Two-Dimensional Difference Gel Electrophoresis (2D-DIGE) Analysis of Three Distinct Proteomes -- Selective Reaction Monitoring for Quantitation of Cellular Proteins -- Characterization of a Protein Interactome by Co-Immunoprecipitation and Shotgun Mass Spectrometry -- Using 15N-Metabolic Labeling for Quantitative Proteomic Analyses -- Multiplex Measurement of Serum Folate Vitamers by UPLC-MS/MS -- UPLC-MS/MS Determination of Deuterated 25-Hydroxyvitamin D (d3-25OHD3) and Other Vitamin D Metabolites for the Measurement of 25OHD Half-Life -- iTRAQ-Based Shotgun Proteomics Approach for Relative Protein Quantification -- 1H NMR Metabolomic Profiling of Human and Animal Blood Serum Samples -- Lab-on-a-Chip Multiplex Assays -- Multiplex Smartphone Diagnostics -- Development of a User-Friendly App for Assisting Anticoagulation Treatment -- Multiplex Biomarker Approaches to Enable Point-of-Care Testing and Personalized Medicine.